2016
DOI: 10.2337/dc15-2666
|View full text |Cite
|
Sign up to set email alerts
|

Specialist-Led Diabetes Registries and Prevalence of Poor Glycemic Control in Type 2 Diabetes: The Diabetes Registry Outcomes Project for A1C Reduction (DROP A1C)

Abstract: OBJECTIVETo highlight the utility of a large patient registry to identify functionally refractory patients (persistent HbA 1c ‡75 mmol/mol [9.0%]) with type 2 diabetes, identify their barriers to glycemic control, and implement barrier-specific care path strategies to improve glycemic control. RESEARCH DESIGN AND METHODSA working group developed a structured tool to optimize the collection of information on barriers to glycemic control and designed structured care paths to address each barrier. Participants we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
3
18
1
Order By: Relevance
“…Poor glycaemic control is expected to become more prevalent later in life due to limited physical activity or nonadherence to treatment [22,25]. There was, nevertheless, no significant association between age and glycaemic control in the current study ( Table 2).…”
Section: Discussioncontrasting
confidence: 51%
“…Poor glycaemic control is expected to become more prevalent later in life due to limited physical activity or nonadherence to treatment [22,25]. There was, nevertheless, no significant association between age and glycaemic control in the current study ( Table 2).…”
Section: Discussioncontrasting
confidence: 51%
“…The LMC Skills, Confidence & Preparedness Index was developed in response to several needs in patient education. An assessment tool that could better identify specific patient gaps and barriers would allow better individualization of support strategies and teaching, as recently demonstrated in the DROP A1C study [5]. A tool that could measure patient confidence and preparedness, beyond just current behaviour, and still correlate consistently to accepted clinical outcomes, such as glycemic control, would allow better triaging of patients into appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The unique challenge to optimal diabetes self-care, is the requisite integration of multiple skills and behavioural changes. The recent Diabetes Registry Outcomes Project for A1C Reduction (DROP A1C) study [5] of refractory patients used the Barriers to Care Index and found that when barriers were correctly identified, individualized care paths could be successfully implemented, and significant improvements in previously refractory glycemic control were possible. Interestingly, no one barrier or barrier category (psychological/support, socioeconomic, comorbidity, accessibility, cultural) was associated with greater likelihood of response, implying that each barrier could be equally overcome with appropriate care path individualization.…”
Section: Introductionmentioning
confidence: 99%
“…The registry contains sociodemographic information, medical history, prescriptions and laboratory investigations. A detailed description of this registry has been previously described (8,9). Patients provided written consent for their electronic medical records to be used for research purposes, and this study was approved by a local ethics review board.…”
Section: Methodsmentioning
confidence: 99%